Characterization of influenza seasonality in China, 2010–2018: Implications for seasonal influenza vaccination timing. Issue 6 (5th September 2022) - Liao, Yilan; Xue, Shan; Xie, Yiran; Zhang, Yanping; Wang, Dayan; Zhao, Tong; Du, Wei; Chen, Tao; Miao, Hui; Qin, Ying; Zheng, Jiandong; Yang, Xiaokun; et al.
Abstract: Background: Optimizing the timing of influenza vaccination based on regional temporal seasonal influenza illness patterns may make seasonal influenza vaccination more effective in China. Methods: We obtained provincial weekly influenza surveillance data for 30 of 31 provinces in mainland China from the Chinese Center for Disease Control and Prevention for the years 2010–2018. Influenza epidemiological regions were constructed by clustering analysis. For each region, we calculated onset date, end date, and duration of seasonal influenza epidemics by the modified mean threshold method. To help identify initial vaccination target populations, we acquired weekly influenza surveillance data for four age groups (0–4, 5–18, 19–59, and ≥60 years) in each region and in 171 cities of wide‐ranging size. We used linear regression analyses to explore the association of epidemic onset dates by age group, city, and epidemiological region and provide evidence for initial target populations for seasonal influenza vaccination. Results: We determined that northern, mid, southwestern, southeast regions of mainland China have distinct seasonal influenza epidemic patterns. We found significant regional, temporal, and spatial heterogeneity of seasonal influenza epidemics. There were significant differences by age group and city size in the interval between epidemic onset in the city or age group and regional spread (epidemic lead time), with longer epidemic lead times for 5‐ to 18‐year‐old children and larger cities. Conclusions: Knowledge of influenza epidemic characteristics may help optimize local influenza vaccination timing and identify initial target groups for seasonal influenza vaccination in mainland China. Similar analyses may help inform seasonal influenza vaccination strategies in other regions and countries.